Fibroids and unexplained infertility treatment with epigallocatechin gallate: a natural compound in green tea (FRIEND) – protocol for a randomised placebo-controlled US multicentre clinical trial of EGCG to improve fertility in women with uterine fibroids - Hao Huang; Heping Zhang; James H Segars; Ayman Al-Hendy; Hugh S Taylor; Frank González; Hiba Siblini; Musa Zamah; Hiba Alkelani; Bhuchitra Singh; Valerie A Flores; Gregory M Christman; et al. (BMJ Open, 2024)
Introduction Uterine fibroids affect 30%–77% of reproductive-age women and are a significant cause of infertility. Surgical myomectomies can restore fertility, but they often have limited and temporary benefits, with postoperative complications such as adhesions negatively impacting fertility. Existing medical therapies, such as oral contraceptives, gonadotropin hormone-releasing hormone (GnRH) analogues and GnRH antagonists, can manage fibroid symptoms but are not fertility friendly. This study addresses the pressing need for non-hormonal, non-surgical treatment options for women with fibroids desiring pregnancy. Previous preclinical and clinical studies have shown that epigallocatechin gallate (EGCG) effectively reduces uterine fibroid size. We hypothesise that EGCG from green tea extract will shrink fibroids, enhance endometrial quality and increase pregnancy likelihood. To investigate this hypothesis, we initiated a National Institute of Child Health and Human Development Confirm-funded trial to assess EGCG’s efficacy in treating women with fibroids and unexplained infertility.Methods and analysis This multicentre, prospective, interventional, randomised, double-blinded clinical trial aims to enrol 200 participants with fibroids and unexplained infertility undergoing intrauterine insemination (IUI). Participants will be randomly assigned in a 3:1 ratio to two groups: green tea extract (1650 mg daily) or a matched placebo, combined with clomiphene citrate-induced ovarian stimulation and timed IUI for up to four cycles. EGCG constitutes approximately 45% of the green tea extract. The primary outcome is the cumulative live birth rate, with secondary outcomes including conception rate, time to conception, miscarriage rate, change in fibroid volume and symptom severity scores and health-related quality of life questionnaire scores.Ethics and dissemination The FRIEND trial received approval from the Food and Drug adminstration (FDA) (investigational new drug number 150951), the central Institutional Review Board (IRB) at Johns Hopkins University and FRIEND-collaborative site local IRBs. The data will be disseminated at major conferences, published in peer-reviewed journals and support a large-scale clinical trial.Trial registration number NCT05364008.